High resolution wide field surface plasmon microscopy - Stabler, Graham (2005)
This thesis presents the development of a high resolution wide field speckle illuminated interferometric surface plasmon microscope. This system is based on a Linnik interferometer and uses a high NA oil immersion objective for the excitation of surface plasmons. The confocal response of the microscope and high surface field enhancement due to surface plasmon excitation lead to high resolution and high contrast of weak surface structures and films. The microscope was also demonstrated in two other modes of operation, a sensing mode where the distributions seen in the back focal plane of the sample objective could be used to determine the optical parameters of the sample and a conventional surface plasmon microscope mode where image enhancement was created through the use of polarizers and optical masks. Results are presented that show the microscope as capable of imaging results comparable or better than that in the literature and without the need to scan. Hence the system is shown to be wholly suitable to biological and research fields interested in thin films and surface reactions.